Ottoman Cash Waqf System: An Alternative to the Western Capitalist System - Izzatul Muna; Yasdi (University of Darussalam Gontor, 2023)
The purpose of this article is to investigate and analyze the Ottoman cash waqf system as a distinct economic model from capitalism, concentrating on its principles, operational mechanisms, and social impact. This study employed a literature review methodology and compared the Ottoman currency waqf system to the western capitalist system. This study reveals that the Ottoman cash waqf system was founded on the principles of social justice, solidarity, and equitable distribution, as opposed to the capitalist principles of prioritizing individual gain. This system provides solutions to problems of social and economic inequality and safeguards the most vulnerable members of society. In spite of its positive potential, the Ottoman cash waqf system confronts a number of obstacles, such as lack of effective management, proper regulation, and public awareness. This article explores the potential of the Ottoman cash waqf system as a different response to social and economic challenges that are viewed as an attractive alternative to the western capitalist system, despite the fact that the western capitalist system can have negative systemic effects.